2022
DOI: 10.1073/pnas.2121663119
|View full text |Cite
|
Sign up to set email alerts
|

Natural disaster and immunological aging in a nonhuman primate

Abstract: Weather-related disasters are increasing in frequency and severity, leaving survivors to cope with ensuing mental, financial, and physical hardships. This adversity can exacerbate existing morbidities, trigger new ones, and increase the risk of mortality—features that are also characteristic of advanced age—inviting the hypothesis that extreme weather events may accelerate aging. To test this idea, we examined the impact of Hurricane Maria and its aftermath on immune cell gene expression in large, age-matched,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 95 publications
1
35
1
Order By: Relevance
“…In order to investigate how gene expression related to the neopterin and suPAR phenotypes changes across age, we used gene expression data collected as part of an ongoing study. The complete dataset has been published and described in detail elsewhere (Watowich et al, 2022). In brief, whole blood was drawn from sedated rhesus macaques by veterinary staff.…”
Section: Blood Collection Rna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate how gene expression related to the neopterin and suPAR phenotypes changes across age, we used gene expression data collected as part of an ongoing study. The complete dataset has been published and described in detail elsewhere (Watowich et al, 2022). In brief, whole blood was drawn from sedated rhesus macaques by veterinary staff.…”
Section: Blood Collection Rna Extraction and Sequencingmentioning
confidence: 99%
“…The ages of these individuals at the time of sampling ranged from 3 to 28 years, with an average age of 8.6 years. A detailed description of RNA extraction and sequencing protocols is provided in Watowich et al (2022). In short, RNA from 457 samples was extracted using MagMAX for Stabilized Blood Tubes RNA Isolation Kits (Thermo Fisher; Cat.…”
Section: Blood Collection Rna Extraction and Sequencingmentioning
confidence: 99%
“…Following this extreme weather event, individuals increased their number of social connections on the island, illustrating how the species may use social buffering to mitigate the negative consequences of major anthropogenic events ( Testard et al, 2021 ). Additionally, while hurricanes on the island population have had a significant effect on patterns of gene expression ( Watowich et al, 2022 ) , female rhesus macaques have been shown to increase their fertility later in life such that their lifetime reproductive success is not affected by these events ( Morcillo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Importantly, the aging process of rhesus monkeys is highly similar to that of humans, including declines in physical health, physiological integrity, brain function, and peripheral immune regulation. 9-11…”
Section: Introductionmentioning
confidence: 99%
“…9 Importantly, the aging process of rhesus monkeys is highly similar to that of humans, including declines in physical health, physiological integrity, brain function, and peripheral immune regulation. [9][10][11] Ocular studies of rhesus macaques have shown close anatomical association between NHP and human visual systems, including features of the optic nerve head, retina, and lens. 8,12,13 While those similarities are well established, detailed data on how aging impacts ocular structures in macaques remain limited to a few studies based on small (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%